2022
DOI: 10.26444/aaem/149469
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of target organ damage in hypertensive patients with coexisting obstructive sleep apnea

Abstract: Introduction and Objective.Obstructive sleep apnea (OSA) is associated with cardiovascular risk and higher mortality. Assessment of subclinical organ lesions is significant for prevention of clinically manifested complications which might result in death. The aim of the study was to assess the prevalence of subclinical target organ damage in hypertensive patients with OSA, and to establish whether these lesions are dependent on the intensity of sleep-disordered breathing. Materials and method. The study covere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In the same line, studies by Altin et al ( 35 ) and Wang et al ( 36 ) described an association of cIMT with severe OSA and AHI. Conversely, Myśliński et al ( 37 ) described absence of differences in early lesions between severe OSA patients and healthy controls. However, patients with COPD have increased vascular damage compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
“…In the same line, studies by Altin et al ( 35 ) and Wang et al ( 36 ) described an association of cIMT with severe OSA and AHI. Conversely, Myśliński et al ( 37 ) described absence of differences in early lesions between severe OSA patients and healthy controls. However, patients with COPD have increased vascular damage compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with OSA may present with a variety of symptoms, including habitual snoring, fatigue, poor sleep quality, excessive daytime sleepiness (EDS), memory loss, headaches, and psychological disturbances ( 3 ). Many studies have confirmed that untreated OSA can damage multiple systems and organs and cause a variety of complications, including cardiovascular diseases, ischemic stroke, metabolic-related diseases, and neuropsychiatric complications ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%